IMPLEMENTASI MEDIA GAME BOOK GIVING QUESTION AND GETTING ANSWER (Q&A) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VII DI SMPN 1 SUMBERREJO - Nurul Laily Nilam Rahmawati; Khoirotus Silfiyah; Aya Mamlu’ah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This study aims to describe the implementation of the Game Book media based on the Giving Question and Getting Answer (Q&A) model in improving student learning outcomes in Islamic Religious Education (PAI) for seventh-grade students at SMPN 1 Sumberrejo, as well as to identify the supporting and inhibiting factors in its application. This research used a descriptive qualitative approach, with data collected through observation, interviews, and documentation.The results show that the use of Game Book Q&A media has a positive impact on increasing students' engagement and understanding of the subject matter on rukhsah. The media integrates engaging visual elements with an active learning approach, encouraging students to ask and answer questions, thereby creating a fun, communicative, and participatory learning environment. Students are not merely passive recipients but are actively involved in thinking, discussing, and expressing their ideas independently.The success of this implementation is supported by several factors such as teacher creativity in designing the media, high student enthusiasm, availability of supporting facilities, and the relevance of the material to daily life. Nevertheless, there are challenges that need attention, including varying levels of digital literacy, limited instructional time, and difficulties in maintaining classroom focus and effective interaction. Overall, the Game Book Giving Question and Getting Answer media has great potential to be further developed as an innovative and inspiring learning method in religious education at schools.